Comprehension connections : bridges to strategic reading - McGregor, Tanny (Portsmouth, NH : Heinemann, 2007)
A guide to helping children fully understand texts that explains how teachers can make the comprehension process achievable, accessible, and incremental by creating links between the concrete and the abstract through writing, discussion, song, art, and movement.
Bridge building 101 -- Metacognition : it's the thought that counts -- Schema : your own world wide web -- Inferring : not just anybody's guess -- Questioning : fuel for thought -- Determining importance : under the big top -- Visualizing : see for yourself -- Synthesizing : keep the change -- Epilogue : where the sidewalk begins.
"Foreword by Stephanie Harvey"--Cover.
Text in English.
Includes bibliographical references (pages 119-121) and index.
Keywords: Reading comprehension; Reading, Psychology of; Metacognition in children